2019
DOI: 10.3390/cryst9070342
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Removal and Efficient Recovery of Tetracycline Antibiotics in Aqueous Solution Using Layered Double Hydroxide Components in an In Situ-Adsorption Process

Abstract: This work demonstrates a simple approach for the efficient removal of tetracycline (TC) antibiotic from an aqueous solution. The in situ-adsorption removal method involved instant precipitation formation of mixed metal hydroxides (MMHs), which could immediately act as a sorbent for capturing TC from an aqueous solution, by employing layered double hydroxide (LDH) components including magnesium and aluminum ions in alkaline conditions. By using this approach, 100% removal of TC can be accomplished within 4 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Along with heavy metal pollution, antibiotics increasingly pose a serious concern for environmental water. Panplado et al [5] demonstrated a simple strategy to very rapidly remove tetracycline (TC) antibiotic molecules from contaminated water. They propose an in-situ adsorption method which involves the utilization of Mg 2+ and Al 3+ containing LDH precursors to promote the precipitation of mixed metal hydroxides (MMHs), which act as fast sorbents for capturing TC from aqueous solution.…”
mentioning
confidence: 99%
“…Along with heavy metal pollution, antibiotics increasingly pose a serious concern for environmental water. Panplado et al [5] demonstrated a simple strategy to very rapidly remove tetracycline (TC) antibiotic molecules from contaminated water. They propose an in-situ adsorption method which involves the utilization of Mg 2+ and Al 3+ containing LDH precursors to promote the precipitation of mixed metal hydroxides (MMHs), which act as fast sorbents for capturing TC from aqueous solution.…”
mentioning
confidence: 99%
“…According to previous studies, the adsorption of TC on many adsorbents involves a variety of interactions, such as hydrogen bonds, , surface complexation, , hydrophobic interactions, electrostatic interactions, , and π–π interactions. , The hydrophobic interaction is not the main motivating force for the adsorption of TC by the aluminosilicate zeolite because the zeolite was found to be hydrophilic with a contact angle of 76° (see Figure S2). In addition, the adsorption mechanism may not be π–π interaction because the aluminosilicate zeolite surface does not have a ring structure that promotes the π–π interaction with the ring structure of the TC molecule.…”
Section: Resultsmentioning
confidence: 96%
“…According to previous studies, the adsorption of TC on many adsorbents involves a variety of interactions, such as hydrogen bonds, 21,51 surface complexation, 48,49 hydrophobic interactions, 23 electrostatic interactions, 51,52 and π−π interactions. 23,52 The hydrophobic interaction is not the main motivating force for the adsorption of TC by the aluminosilicate zeolite because the zeolite was found to be hydrophilic with a contact angle of 76°(see Figure S2).…”
Section: Effect Of Cations and Solution Aciditymentioning
confidence: 99%
“…Real water samples coming from a dam, a river, three lakes and a wastewater plant were used by Panplado et al [34] when studying the adsorption capacity of calcined MgAl LDH, synthetized by the co-precipitation method with a 3:1 mol ratio, over TCY. The removal capacity of TCY was superior to 90 % in all cases.…”
Section: Combined Adsorption and Effect Of Foreign Substancesmentioning
confidence: 99%